2006
DOI: 10.1111/j.1466-822x.2006.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter nitrogen concentration as related to climatic factors in Eurasian forests

Abstract: Aim The aim of this study is to determine the patterns of nitrogen (N) concentrations in leaf litter of forest trees as functions of climatic factors, annual average temperature (Temp, ° C) and annual precipitation (Precip, dm) and of forest type (coniferous vs. broadleaf, deciduous vs. evergreen, Pinus , etc.). LocationThe review was conducted using data from studies across the Eurasian continent.Methods Leaf litter N concentration was compiled from 204 sets of published data (81 sets from coniferous and 123 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…A number of studies have attempted to establish relationships between climate factors and N and P concentration for Mean annual temperature ( o C) Latitude the leaf-litter of woody plants at a regional (Aerts, 1997;Liu et al, 2006) and global scale (Aerts, 1997;McGroddy et al, 2004;Yuan and Chen, 2009b). Our study use a new dataset to establish the general patterns in N and P concentrations and N:P ratios in leaf-litter of woody plants at a global level, showing some inconsistent results with previous studies.…”
Section: General Levels Of N P and N:p Ratio In Leaf-litter Of Woodymentioning
confidence: 85%
See 4 more Smart Citations
“…A number of studies have attempted to establish relationships between climate factors and N and P concentration for Mean annual temperature ( o C) Latitude the leaf-litter of woody plants at a regional (Aerts, 1997;Liu et al, 2006) and global scale (Aerts, 1997;McGroddy et al, 2004;Yuan and Chen, 2009b). Our study use a new dataset to establish the general patterns in N and P concentrations and N:P ratios in leaf-litter of woody plants at a global level, showing some inconsistent results with previous studies.…”
Section: General Levels Of N P and N:p Ratio In Leaf-litter Of Woodymentioning
confidence: 85%
“…Aerts (1997) reported that both leaf-litter N and P concentrations follow a positive but non-linear relationship with actual evapotranspiration based on a dataset concerning cool and warm temperate sites, the Mediterranean and the humid lowland tropics. Liu et al (2006) reported that leaf-litter N concentration increased linearly with mean annual temperature (MAT,…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations